Pengaruh Entrepreneurial Marketing Terhadap Kinerja Pemasaran Usaha Mikro Sulam Jahit Kasab di Kecamatan Kuala Baru, Kabupaten Aceh Singkil - Syahruli, Syahruli; Yusnaidi, Yusnaidi; Chairiyaton, Chairiyaton; Putri, Cut Mega (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2024)
Entrepreneurial marketing is a marketing activity carried out by small and medium scale business actors in starting a business. This study aims to determine how much influence entrepreneurial marketing has on marketing performance in kasab embroidery micro businesses in Kuala Baru District, Aceh Singkil Regency. The sampling technique used to collect data through questionnaires to 96 people who sew kasab with the Likert scale method. The method used is simple linear regression analysis. The results show that entrepreneurial marketing has a positive effect on marketing performance as evidenced by the significance value for the effect of the entrepreneurial marketing variable (x) on the marketing performance variable (y) worth 0.000 <0.05 and the value of t count 12.822> t table 0.2006. So it is hoped that every Micro, Small and Medium Enterprises  actor can always set aside part of his profits to be used as the next capital, so that the business he runs can continue to grow.